2020
DOI: 10.1016/j.neuropharm.2020.108234
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to nicotine addiction: Advances and shortcomings in our understanding of the CHRNA5/A3/B4 gene cluster contribution

Abstract: Highlights (85 characters including space each)• CHRNA5/A4/B4 and nicotine addiction link on SNPs in high linkage disequilibrium• CHRNA5/A4/B4 cross-regulatory mechanisms should be considered in preclinical models

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 218 publications
(212 reference statements)
1
11
0
1
Order By: Relevance
“…In our application analysis, Dense-LD identified causal variants from different haplotype blocks in an extended genomic region of 1733 SNPs on chromosome 15. The genes of these causal variants (e.g., IREB2, CHRNA3, CHRNA5, CHRNB4, and HYKK) are related to smoking-related diseases and functionally correlated [8,11,72,73]. Our method showed that the selected SNPs from these genes are strongly correlated, although many are distant.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In our application analysis, Dense-LD identified causal variants from different haplotype blocks in an extended genomic region of 1733 SNPs on chromosome 15. The genes of these causal variants (e.g., IREB2, CHRNA3, CHRNA5, CHRNB4, and HYKK) are related to smoking-related diseases and functionally correlated [8,11,72,73]. Our method showed that the selected SNPs from these genes are strongly correlated, although many are distant.…”
Section: Discussionmentioning
confidence: 90%
“…Thousands of diseases-associated genetic loci have been discovered and replicated [2,3,9,10]; however, even replicated loci may differ from the causal variants due to linkage disequilibrium (LD) among proximal and distant loci. Specifically, non-causal variants can be associated with a trait because of the high correlation with the causal variants due to LD [4,11,12]. Hence, a post-hoc examination of trait associations is required to distinguish likely causal variants from those associated with the trait.…”
Section: Fine-mapping and Existing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…La dépolarisation membranaire qui en résulte entraîne par exemple la contraction de la cellule musculaire, ou la libération de neurotransmetteurs par les neurones du cerveau. Les récepteurs nicotiniques neuronaux sont notamment responsables de l'addiction au tabac, qui implique le circuit dopaminergique de la récompense [7]. Nous avions précédemment décrit l'expression des dif-férentes sous-unités des récepteurs nicotiniques dans le poumon humain [8].…”
Section: Récepteur Nicotinique De L'acétylcholine Et Bronchopneumopat...unclassified
“…Identification of DNA sequences for these genes led to efforts to identify variation in these genes that could be used for linkage and association studies, most commonly single nucleotide polymorphisms (SNPs). The cumulative findings of candidate gene studies of drug dependence have been extensively reviewed many times [Kreek et al, 2005;Gelernter and Kranzler, 2009;Jones and Comer, 2015], including reviews that focus upon particular substances [Stickel et al, 2017;Icick et al, 2020;Thorpe et al, 2020]. Many reviews have tended to indicate that there are greater degrees of concordance between studies than have actually been observed.…”
Section: Candidate Gene Studies: Guessing Which Genes Are Important For Addictionmentioning
confidence: 99%